OPTIMALISASI SARANA DAN PRASARANA EDUKATIF UNTUK PENINGKATKAN EFEKTIFITAS PEMBELAJARAN DI BIMBEL INTEGRAL INSTITUTE - Misbahul Huda; Awatif; Muhammad Jainuri; Ade Susanti; Sugeng Riyadi (AbdiMasya | Hira Institute, 2025)
The utilization of facilities and infrastructure at the Integral Institute Tutoring Institute, Sungai Ulak District, Nalo Tantan District, Merangin Regency is the focus of this research. This research aims to determine how the facilities and infrastructure at the madrasah are utilized to improve the quality of learning and provide recommendations for optimizing their utilization. This research uses a qualitative approach with a case study method to understand in detail the utilization of facilities and infrastructure at the Integral Institute Tutoring Institute, Sungai Ulak District, Nalo Tantan District, Merangin Regency. The results of the research are expected to assist the institution's management in planning the development of more effective facilities and infrastructure and improving the quality of learning. In addition, this research can be an example for other tutoring institutions in optimizing the utilization of educational facilities and infrastructure. Although the Integral Institute Tutoring Institute, Sungai Ulak District, Nalo Tantan District, Merangin Regency does not yet have complete facilities and infrastructure and internet access, there is still great potential to improve the quality of learning through optimal utilization of existing facilities and infrastructure. This study aims to provide a deeper understanding of the utilization of facilities at the Integral Institute Tutoring Center in Sungai Ulak District, Nalo Tantan Regency, Merangin Regency, and how this utilization can be improved to achieve better learning quality. This research is also expected to serve as a reference for other madrasahs in optimizing the use of educational facilities and infrastructure.